THE EFFECTS OF SERVICE QUALITY, CUSTOMER SATISFACTION, TRUST, AND PERCEIVED VALUE TOWARDS CUSTOMER LOYALTY - Tanisah, Tanisah; Maftukhah, Ida (Department of Management, Faculty of Economics, Semarang State University, Indonesia, 2015)
This purpose of the research is to examine the effects of service quality, customer satisfaction, trust, and perceived value towards customer loyalty in KJKS BMT Bondho Tumoto Semarang. The sample was taken by using incidental sampling techniques and it had 98 customers. The data was analyzed by multiple linier regressions. Test results in partial show that service quality, trust and perceived value gave positive and significant effect towards customersâ loyalty. In contrast, customer satisfaction did not have significant effect towards customersâ loyalty. Then, simultaneous testing show that service quality, customer satisfaction, trust and perceived value gave significant effects towards customersâ loyalty. This study found that from those variables, trust variable gave the biggest effect towards customersâ loyalty.